2005
DOI: 10.1111/j.1748-5827.2005.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonaemic encephalopathy secondary to selective cobalamin deficiency in a juvenile Border collie

Abstract: An eight-month-old Border collie was presented with anorexia, cachexia, failure to thrive and stupor. Laboratory tests demonstrated a mild anaemia, neutropenia, proteinuria and hyperammonaemia. Serum bile acid concentrations were normal, but an ammonia tolerance test (ATT) was abnormal. The dog responded to symptomatic therapy for hepatoencephalopathy. When a low serum cobalamin (vitamin B12) concentration and methylmalonic aciduria were noted, the dog was given a supplement of parenteral cobalamin. Two weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 13 publications
(6 reference statements)
3
60
0
1
Order By: Relevance
“…Both cases presented with normocytic, normochromic, non-regenerative anaemia, compatible with previous reports in hypocobalaminaemic Beagles (Fordyce and others 2000, Fyfe and others 2014) and Border collies (Battersby and others 2005, Lutz and others 2013). Case 1 also had thrombocytopenia with hypersegmented neutrophils seen on examination of mesenteric lymph node aspirates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both cases presented with normocytic, normochromic, non-regenerative anaemia, compatible with previous reports in hypocobalaminaemic Beagles (Fordyce and others 2000, Fyfe and others 2014) and Border collies (Battersby and others 2005, Lutz and others 2013). Case 1 also had thrombocytopenia with hypersegmented neutrophils seen on examination of mesenteric lymph node aspirates.…”
Section: Discussionsupporting
confidence: 91%
“…Cerebrospinal fluid and synovial fluid were not sampled in Case 1 because of concurrent thrombocytopenia, but a diagnosis of inflammatory meningitis or arthropathy seems unlikely based on the rapid complete response to cobalamin supplementation. Finally, another sign that both sets of owners described was lethargy, and this sign has been described in both Beagles and other breeds with hypocobalaminaemia (Morgan and others 1999, Battersby and others 2005, Lutz and others 2013, Kook and others 2015). …”
Section: Discussionmentioning
confidence: 83%
“…This is a rare autosomal recessive disorder which, if left untreated, results in failure to thrive, megaloblastic anemia, proteinuria, and neurological damage 2. In dogs, primary cobalamin malabsorption, which is analogous to IGS in humans, has been reported in young Australian Shepherds,3 a Beagle,4 Border Collies,5, 6, 7 and Giant Schnauzers 8. The genetic defects in affected Border Collies and Beagles recently have been identified as 2 independent mutations in the CUBN gene 9, 10.…”
mentioning
confidence: 99%
“…The genetic defects in affected Border Collies and Beagles recently have been identified as 2 independent mutations in the CUBN gene 9, 10. Similar to human patients, dogs typically present at a young age with inappetence, weakness, and failure to thrive 4, 5, 6, 8, 11. Although liver disease is recognized in cobalamin‐deficient farm animals, especially lambs,12, 13 it has not been reported in dogs suffering from hereditary cobalamin malabsorption.…”
mentioning
confidence: 99%
“…As previously reported by Fordyce et al (2000), this patient was successfully treated by parenteral vitamin B12 administration every 2-4 weeks. Cobalamin malabsorption has also been described in giant Schnauzers (Fyfe et al, 1991), Border collies (Battersby et al, 2005), and Australian shepherd dogs (He et al, 2005). Investigations of affected Giant schnauzers and Australian shepherd dogs at the molecular level (Fyfe et al, 2004;He et al, 2005) have confirmed that this disease is a true homologue of congenital megaloblastic anaemia due to vitamin B12 deficiency because of a defect in the vitamin B12/intrinsic factor receptor (Imerslund-Gräsbeck syndrome) in humans.…”
Section: Diagnostic Proceduresmentioning
confidence: 66%